Histones as mediators of host defense, inflammation and thrombosis. (March 2016) - Hoeksema, Marloes; van Eijk, Martin; Haagsman, Henk P; Hartshorn, Kevan L
Histones are known for their ability to bind to and regulate expression of DNA. However, histones are also present in cytoplasm and extracellular fluids where they serve host defense functions and promote inflammatory responses. Histones are a major component of neutrophil extracellular traps that contribute to bacterial killing but also to inflammatory injury. Histones can act as antimicrobial peptides and directly kill bacteria, fungi, parasites and viruses, in vitro and in a variety of animal hosts. In addition, histones can trigger inflammatory responses in some cases acting through Toll-like receptors or inflammasome pathways. Extracellular histones mediate organ injury (lung, liver), sepsis physiology, thrombocytopenia and thrombin generation and some proteins can bind histones and reduce these potentially harmful effects.